DESAIN TRACER DI UPT PUSKESMAS CITARIP KOTA BANDUNG - Tria Haguna; Muni Widya Hidayati; Yuyun Yunengsih (LPSDI Bina Patria, 2022)
Abstract The availability of medical record documents quickly and accurately will greatly affect the quality of health services for patients. If the storage of medical record documents used is not good, there will be many problems that will affect the availability of medical record documents. Therefore, the storage of medical records is very important to note. To assist in the availability of medical record documents, one of which is needed is a tracer (exit instructions). The purpose of this study is to provide an overview of the tracer design (exit instructions) at UPT Puskesmas Citarip Bandung City to make it easier to minimize the loss of medical record documents (missfiles) and also to simplify the process of storing (filing) medical records. This research method uses qualitative analysis. with a descriptive approach with data collection techniques of observation, interviews, and documentation studies. The results of the Tracer design (exit instructions) of the selected medical record are using Alternative II with a length of 40 cm and a width of 11 cm made of thick cardboard covered with 150g glossy laminated print artpaper using red color so that it can distinguish it from existing medical record documents accompanied by a bag with a size of 10 cm long and 9 cm wide serves to store loan receipts.